Industrial revolution / with a preface by F. York Powell - Beard, Charles (London, 1936)
Owing to the unity of all history, we are compelled to define arbitrarily and set limits when any special field is undertaken. Industrial History is the story of man's labour with tools and mechanical and power appliances for the satisfaction of his wants. By the Industrial Revolution we mean that great trans formation which has been brought about during the past one hundred and fifty years, by discoveries and inventions which have altered fundamentally all the methods of production and distribution of the means of life, and consequently revolutionised all the economic functions of society. Man, who through the long centuries had toiled with his hands, aided by crude implements, to wrest a pitiful subsistence from Nature, suddenly discovered that the blind forces against which he had been struggling could be chained to do his work.
Keywords: Industry-History